2004
DOI: 10.4161/cc.3.8.1062
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Link Between DNA Polymerase Beta and Cancer?

Abstract: Cells transduce mechanical forces into biochemical signals; traditionally these processes are thought to occur through direct effects on the cell membrane, the cytoskeleton, or specific transmembrane proteins. In multicellular tissues mechanical forces alter intercellular spacing through redistribution of interstitial fluid. Recent morphological and biochemical observations, bolstered by analytical modeling, support a new paradigm for mechanotransduction arising from constitutive growth factor shedding into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
218
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(222 citation statements)
references
References 25 publications
3
218
0
1
Order By: Relevance
“…Given the role of pol in maintaining genome integrity and the relation between pol 's malfunction and various diseases (e.g., cancer, premature aging), [50][51][52] pol has attracted many experimental (see ref 53 and references therein) and theoretical investigations. 8,54,[55][56][57] Our prior modeling work of the pol dynamics before and after the chemical step of nucleotidyl transfer reaction using MD 48,[58][59][60][61] and transition path sampling (TPS) 22 employed the CHARMM force field.…”
Section: Introductionmentioning
confidence: 99%
“…Given the role of pol in maintaining genome integrity and the relation between pol 's malfunction and various diseases (e.g., cancer, premature aging), [50][51][52] pol has attracted many experimental (see ref 53 and references therein) and theoretical investigations. 8,54,[55][56][57] Our prior modeling work of the pol dynamics before and after the chemical step of nucleotidyl transfer reaction using MD 48,[58][59][60][61] and transition path sampling (TPS) 22 employed the CHARMM force field.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the literature 10 indicated that Pol β variants are present in 30% of tumors analyzed to date, but these variants are not present in normal tissue from the same patients. Each of the tumors studied also express the wild type Pol β protein.…”
Section: Pol β β Tumor-associated Variants Are Linked To Cancer Etiologymentioning
confidence: 99%
“…The MBD4 gene maps to chromosome 3q21-22, 35 and the MBD4 protein interacts with MLH1, alteration of which is known to result in HNPCC. 36 Importantly, the MBD4 gene contains one polyA (10) and three polyA (6) repeat tracts in exon 3 within the coding region of the gene. 37,38 Tumors resulting from alteration of mismatch repair genes and with high levels of microsatellite instability (MSI-H) synthesize a truncated MBD4 protein due to mutation of these repeats, as shown in Table 1.…”
mentioning
confidence: 99%
“…In 30% cases of cancer, pol beta has mutation (Chen et al 2002;Starcevic et al 2004). Leu22Pro tumor-associated variant of polβ is dRP lyase deficient (Dalal et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…If the polβ protein is being mutated then the function will be altered. It has been noted that more than 30% of the tumor samples studied so far have polβ mutation (Starcevic et al, 2004;Trivedi et al, 2008). Pol β variants, K289M and I260M have functional phenotypes that could be related to the etiology of human cancer (Lang et al, 2003;Dalal et al, 2005).…”
Section: Introductionmentioning
confidence: 99%